Morphological Variation of Diospyros spp. Native to Sulawesi Based on Vegetative Organ Characters - Wulandari, Aprilia Ayu; Khotimperwati, Lilih; Wanda, Irvan Fadli (Universitas Gadjah Mada, 2024)
Researchers about Diospyros have not extensively conducted studies on the morphological characteristics to enhance information for taxonomic hierarchy purposes. Diospyros in Indonesia has great potential for in-depth research due to its unique characteristics, particularly in Sulawesi. This research aims to fill the knowledge gap regarding investigating phenotypic variations in Diospyros, specifically in the Sulawesi region. Nine species of Diospyros from the BBG collection will be observed and described for their morphological characteristics. The results indicate 25 variations of 50 characters in morphological characteristics. Variations in morphological characters can suggest that each species adapts to the surrounding environmental conditions.